An Investigation of Output Variance Before and During Inflation Targeting - Nadal De Simone, Francisco (IMF Working Papers; Working Paper ;, 2001)
Since Taylor estimated a trade-off between inflation and output variance, it has been widely accepted that efforts to keep the inflation rate 'too low and stable' will likely result in relatively larger output fluctuations. Following the generalized reduction in inflation variance in the 1990s, that concern was rekindled. This study estimates whether conditional output variance has changed in a sample of 12 countries. With the possible exception of Canada, there is no evidence of an increase in output variance. Either output variance has not changed (i.e., in Korea and Singapore) or has fallen (i.e., in Australia and New Zealand).